Lives Elsewhere : Migration and Psychic Malaise - Losi, Natale, 1947- (International series of psychosocial perspectives on trauma, displaced people, and political violence., 2006)
Born from the author's desire to write a clear and simple account of complex material based on ethnopsychotherapy and migrations, this book aims to clarify some key questions, rather than serve as a definitive text. It will be of interest to ethnopsychotherapists, to those working with refugees or immigrants, or those interested in the issues of migration and wishing to gain a greater understanding of our multi-cultural world.